(NaTLAS sssr (B:s [(NkARTY(B] /s - (NtO^ENOW(B, (Nw(B.(Nw(B.s ((NmOSKWA (B:s (Ngugk(B,s, 1983)
(NkOMPLEKSNYJ ATLASs
(NsPRAWO^NYE SWEDENIQ(B: (NS(B. 204-206s
(NuKAZATELX GEOGR(B. (NNAZW(B.: (NS(B. 207-259s
Keywords: (NnAUKI O zEMLE (B((NGEODEZI^ESKIE(B, (NGEOFIZI^ESKIE(B, (NGEOLOGI^ESKIE I GEOGRAFI^ESKIE NAUKI(B)s